2012
DOI: 10.1038/srep00980
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear localization of folate receptor alpha: a new role as a transcription factor

Abstract: Folic acid (FA) has traditionally been associated with prevention of neural tube defects; more recent work suggests that it may also be involved in in the prevention of adult onset diseases. As the role of FA in human health and disease expands, it also becomes more critical to understand the mechanisms behind FA action. In this work we examined the hypothesis that folate receptor alpha (FRα) acts as a transcription factor. FRα is a GPI-anchored protein and a component of the caveolae fraction. The work descri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
92
1
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 94 publications
(99 citation statements)
references
References 34 publications
(50 reference statements)
5
92
1
1
Order By: Relevance
“…Therefore, it is also possible that downregulation of FR could account, in part, for acquired vintafolide resistance observed in the clinic. Other unexpected effects may also occur due to FR1's recently identified role as a transcription factor with promoter activity that responds to intracellular folate levels (27). In addition, mRNA levels do not always reflect protein levels, so the relationship between ABCB1 mRNA expression and translation into P-gp would need to be examined in tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is also possible that downregulation of FR could account, in part, for acquired vintafolide resistance observed in the clinic. Other unexpected effects may also occur due to FR1's recently identified role as a transcription factor with promoter activity that responds to intracellular folate levels (27). In addition, mRNA levels do not always reflect protein levels, so the relationship between ABCB1 mRNA expression and translation into P-gp would need to be examined in tumors.…”
Section: Discussionmentioning
confidence: 99%
“…FRα levels are high in specific malignant tumors of epithelial origin compared to normal cells [3,20]. A recent study by Boshnjaku et al, [11] 2012 showed that FRα transcriptionally regulates several Pax3 downstream target genes such as Hes1 (a stem cell maintenance gene) and Fgfr4, suggesting FRα might confer a growth advantage to the tumor by generating transcriptionally regulatory signals. Cell culture studies show that expression of FOLR1 which codes for FRα is regulated by extracellular folate depletion, increased homocysteine accumulation [55], and steroid hormone concentrations [56].…”
Section: Folate Receptor Alpha In Cancer and Its Use In Targeting Canmentioning
confidence: 99%
“…Free FRα translocates into the nucleus where it binds to cisregulatory elements of target genes and directly activates transcription [11] of Hes1 and Fgfr4. This novel role of FRα as a transcription factor is very significant because it provides insight into developmental mechanisms associated with FA responsiveness.…”
Section: Folate Receptor Alpha As a Transcription Factormentioning
confidence: 99%
See 2 more Smart Citations